Analisis Hambatan Pembelajaran Bahasa Indonesia di Sekolah Dasar - Khoiruman, Muhamad (Kajian Linguistik, 2021)
Learning Indonesian in elementary school can help students to get to know themselves, their culture and other cultures, express ideas, participate in society, and discover and use their analytical and imaginative abilities. In the implementation of Indonesian language learning, there are many gaps, so that it is less able to achieve the learning objectives that have been determined optimally. This research was conducted in class 5 SDN Tegalsari 1 Banyuwangi, East Java, Indonesia. The purpose of this study was to determine the obstacles in the process of learning Indonesian in elementary schools. This research uses a case study approach. Data was collected by observing the Indonesian language learning process, interviews, and checking the average test scores of students. The data collected were analyzed using interactive analysis according to Miles and Huberman. The results of the research are 1) Teachers have not used media in the learning process, especially learning Indonesian; 2) The learning carried out is still conventional; 3) Students in learning tend to memorize the subject matter. Through learning innovations that are in accordance with the characteristics of elementary school students, it is expected to be able to create meaningful learning.